The Role of the Village Government in Efforts to Equalize Infrastructure Development in Sungai Rimbang Village, Suliki District, Lima Puluh Kota Regency - Regina Defitri; Rizki Syafril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Equitable development can be defined as a governmental initiative aimed at expanding public access to infrastructure and facilities that align with the needs of the community., equalize public and social facilities, and improve the overall quality of life. This research is intended to analyze the role of the Village Government in efforts to ensure equitable infrastructure development in Sungai Rimbang Village, Suliki District, Lima Puluh Kota Regency. The background of this research is the persistence of disparities in infrastructure development between hamlets in Sungai Rimbang Village, particularly the discrepancy between development plans in the Village Government Work Plan (RKP) and implementation on the ground. Data from 2024 shows that of a number of planned activities, only a small portion has been realized, and some hamlets have not even received any development at all. This study uses a descriptive qualitative method with the approach of the government role theory from Labolo (2010:32), which includes the roles of regulator, catalyst, and facilitator. The results show that the government has formulated regulations such as the RPJM and RKP Village, but implementation and evaluation are still not optimal. Musrenbang (Regional Development Planning) has been implemented as a form of public participation, but the level of community involvement is still low. The government has also facilitated physical development, but its distribution is not equitable. Therefore, it is necessary to increase development effectiveness through regular regulatory evaluation, strengthening community participation, and coordination between village institutions.